Sistema Nacional de Educação e projeto de educação para o país: concepções, proposições e disputas - Araujo, Walisson Maurício de Pinho (2019)
The study developed is an effort to update the debate on the organization of Brazilian education, its standardization and the relations with public education policies, in the form of a National Education System - SNE with binding cooperation norms. Taking as its focus documentary research, in a broad sense, involving the survey and analysis of written and oral documents (interviews), this research aimed to analyze, through content appreciation with the support of historical-dialectical materialism, to what extent federal government (Lula-Dilma) and those embodied in the Legislative in relation to the SNE are related and consistent with the propositions and conceptions contained in the party-coalition government programs and the Education Conferences. Throughout the research work we can see a resumption, with vigor and high levels of institutionality, of discussions about a National Education System, in government and in the National Education Forum - FNE, more organically, and also in the legislative power. With the study, it is possible to understand that the propositions of the Lula and Dilma Governments about the National Education System, notably in the form of a Draft of complementary law and subsidiary texts maintain important level of coherence with the party programs and the Education Conferences. However, the more coordinated efforts of an effective instituting agenda were hampered by changes in direction in the Federal Government, stemming from the impediment of the democratically elected president. These contents and the recent construction processes that mobilized representative entities of the educational field (in FNE) in dialectical relationship with the government, express an important political asset that can drive the resumption of discussions in the National Congress.